Charting the Next Pandemic : Modeling Infectious Disease Spreading in the Data Science Age /: Modeling Infectious Disease Spreading in the Data Science Age. (2018) - Pastore y Piontti, Ana; Perra, Nicola; Rossi, Luca; Samay, Nicole; Vespignani, Alessandro
No abstract available